Continuous post-operative intra-compartmental pressure monitoring after tibial plateau fracture osteosynthesis under regional anesthesia during pregnancy: a case report - Benoît Borner; Vanessa Morello; Axel Gamulin (Trauma Case Reports)
This paper reports the case and management of a 36-year-old female patient, 8 weeks pregnant, who sustained a Schatzker V tibial plateau fracture with a surgical indication. The institutional management protocol consisting of computed tomography imaging to complete standard radiographic workout as well as surgery under general anesthesia was not followed to avoid potential deleterious effects on the fetus. Magnetic resonance imaging and loco-regional anesthesia were preferred. In order to avoid post-operative acute compartment syndrome to develop unnoticed while the effect of the loco-regional anesthesia was still present, a continuous intra-compartmental pressure monitoring device was inserted into the anterior compartment once the surgical fixation was completed and left in place until full recovery of lower limb sensation.